The Postdigital as Theme in Narrative Fiction across Media - Alice Bell (Anglica. An International Journal of English Studies)
This article argues that a sceptical attitude towards the role of digital technology in contemporary life is becoming increasingly prevalent in twenty-first-century fiction and offers a new way of theorising this thematic trend via refining the concept of the ‘postdigital’. Proving a critical overview of the way that the ‘postdigital’ has been interpreted in aesthetics, critical theory, and literary criticism, I show how the scepticism towards digital media that is a tenet of postdigital visual arts can now also be seen in some narrative fiction of the twenty-first century written in English. I thus show how what I define as postdigital fiction interrogates the way in which the digital and nondigital have become hybridised in digitised societies and questions the universal benefits digital media bring. Taking examples from print and digital fiction, I show how a postdigital perspective can manifest both thematically and aesthetically in fiction and argue that there is an increasing prevalence of postdigital ethics in narrative fiction across media.